A Comparison of some Upland and Valley Soils in the Ungava-Labrador Peninsula - Hendershot, William (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1984)
ABSTRACTThirteen soil profiles from northern Québec and Labrador, Canada, near the northern tree-line, were sampled and analysed. Five of these, located on poorly to imperfectly drained sites, are strongly cryoturbated soils with permafrost at a shallow depth. Below the surface horizon they have very uniform profile distributions of pH, carbon and extractable iron and aluminum due to the active mixing of the horizons. The eight soils from well-drained sites have profiles similar to those of soils in similar settings in more temperate climatic regions. One of these, developed in one of the most northerly valleys having a black spruce-larch forest vegetation, has the characteristics of a podzol (spodosol) except that the podzolic B (spodic) horizon is too thin. The other seven profiles all have color B horizons, although the coarse texture prevents their classification as cambic horizons; these soils all have carbon-rich A horizons varying in thickness from 1.5 to 20 cm. Soil temperature at 50 cm depth closely follows the elevational and latitudinal distribution of the soils; a range of 0 to 10° C was observed. Soil development, measured as depth of solum, organic carbon accumulation or degree of B horizon development, is closely related to soil temperature and site position. The presence of permanently frozen ice layers at shallow depth has a marked influence on soil genesis and the properties of the resultant soils.